Sources of Civil and Sports Law as a sub-branch of Civil Law of Ukraine - O. A. Morhunov; I. V. Lysenko; A. M. Lysenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the topical issues of analysis and systematization of sources of Sports and Civil Law. The role of sports in the development of modern society is constantly growing. The development of civil and sports legal relations requires the systematization of the sources of Sports Law, which should harmonize the entire complex of normative legal acts in the field of physical culture and sports. This would make it possible to develop educational programmes for training future specialists in this field, and would raise the legal resolution of disputes in this field to a more professional level.